Effect of Web-Based Education on Self-efficacy and Self-care Ability in Heart Failure Patients - Ratih Arum Vatmasari; Kuswantoro Rusca Putra; Heni Windarwati (Iranian Journal of Nursing and Midwifery Research)
Background: Self-care prevents rehospitalization and reduces mortality from heart failure. The self-care of heart failure patients is influenced by their sense of self-efficacy. Traditional educational methods are time-consuming, require patients to meet with health experts, and frequently cannot be accessed remotely. A web-based educational platform might be one of the innovations included in the development of health education for people with heart failure. The aim of this study is to determine the effect of web-based education on self-efficacy and self-care ability in heart failure patients. Materials and Methods: This study design is quasi-experimental. The study sample consisted of 80 individuals with heart failure with New York Heart Association (NYHA) II-IV classes and separated into two groups: the intervention group (n = 40) and the control group (n = 40). The sampling technique used in this study is consecutive sampling. Self-care is measured using the Self-Care Heart Failure Instrument version. A pre-test was administered before the intervention, and post-test and follow-up were administered two weeks after the intervention. The control group received information leaflets and the intervention group received web-based education. Results: The results showed that the main group effect was significant, indicating a significant increase self-care (F1,80 = 2769, p < 0.001) and self-efficacy (F1,67 = 1600, p < 0.001) in the intervention group after web-based education and two weeks follow-up. Conclusions: Web-based education is more effective in increasing self-efficacy and self-care abilities among heart failure patients. Providing education via a web-based platform in phases and continuously can promote healthy behaviors.